How useful is anthropometric history? Some reflections on Paul Hohenberg's recent presidential address to the American Economic History Association - John Komlos (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2009)
In his recent presidential address to the American Economic History Association, Paul Hohenberg argued that anthropometric history does not meet his criteria for useful research in the field of economic history. He considers research useful if (a) it "helps shape one of our underlying disciplines"; b) it contributes "to clear—even fresh—thinking about current, policy-related issues or on-going scholarly debates about the historical past"; and c) it "penetrates the fuzzy realm of identity-shaping popular discourse". I argue briefly that only a superficial reading of the literature would lead to the conclusion that anthropometric history has not been useful.
urn:nbn:de:bvb:19-epub-10587-3
Keywords: N00; N01; 330; Economic History - General; Economic History - Development of the Discipline: Historiographical; Sources and Methods; Anthropologie; Geschichte; Wirtschaftsgeschichte; Wissenschaftliche Methode; Kritik